Histidine modification with diethyl pyrocarbonate shows heterogeneity of benzodiazepine receptors. - Burch, T P (1981)
The effect of diethyl pyrocarbonate modification of histidine on the specific binding of [3H]diazepam and its enhancement with muscimol and (+/-)-pentobarbital was investigated. Diethyl pyrocarbonate treatment produced a dose-related inhibition of specific [3H]diazepam binding to rat brain membranes with a maximal inhibition of approximately 40% at 1 mM. Scatchard analysis of the binding data showed that diethyl pyrocarbonate, while having no effect on the affinity (Kd), decreased the binding capacity (Bmax) of diazepam from a control value of 1543 +/- 116 fmol/mg of protein to 789 +/- 79 fmol/mg of protein (mean +/- SD; P less than 0.005; n = 4). Under conditions in which approximately 40% of the diazepam binding sites were modified by diethyl pyrocarbonate treatment, the ability of muscimol and pentobarbital to enhance diazepam binding was not altered. These results suggest that a histidine residue is critical for a part (approximately 40%) of the benzodiazepine binding sites and that there may exist a heterogeneity of benzodiazepine binding sites. Furthermore, these results indicate that perhaps only a portion of the benzodiazepine binding sites are functionally coupled to the gamma-aminobutyric acid receptor-ionophore complex.